2016
DOI: 10.18632/oncotarget.8194
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing metformin for cancer treatment: current clinical studies

Abstract: In recent years, several studies have presented evidence suggesting a potential role for metformin in anti-cancer therapy. Preclinical studies have demonstrated several anticancer molecular mechanisms of metformin including mTOR inhibition, cytotoxic effects, and immunomodulation. Epidemiologic data have demonstrated decreased cancer incidence and mortality in patients taking metformin. Several clinical trials, focused on evaluation of metformin as an anti-cancer agent are presently underway. Data published fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
243
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(250 citation statements)
references
References 54 publications
2
243
1
4
Order By: Relevance
“…Hence, methionine restriction metabolically primes breast cancer cells to targeted agents that activate cell death by exposing a targetable vulnerability, namely enhanced cell surface expression of TRAIL-R2. Intriguingly, the diabetes medication metformin mimics many of the effects of methionine restriction, including disruption of methionine metabolism via inhibition of the functionally linked folate cycle in the one-carbon metabolic pathway, inhibition of the mechanistic target of rapamycin (mTOR), broad antitumor activity, improved insulin sensitivity, and prolonged lifespan [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, methionine restriction metabolically primes breast cancer cells to targeted agents that activate cell death by exposing a targetable vulnerability, namely enhanced cell surface expression of TRAIL-R2. Intriguingly, the diabetes medication metformin mimics many of the effects of methionine restriction, including disruption of methionine metabolism via inhibition of the functionally linked folate cycle in the one-carbon metabolic pathway, inhibition of the mechanistic target of rapamycin (mTOR), broad antitumor activity, improved insulin sensitivity, and prolonged lifespan [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin use has been associated with reduced incidence of a broad range of tumor types and reduced cancer mortality in many epidemiologic studies [19][20][21][22]. However, the antitumor mechanisms of metformin are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…There are 3 clinical studies currently evaluating survival benefit of metformin in breast cancer but the results are not obtained yet. 59 The long-term results of these studies may clear up the utility of metformin in cancer treatment.…”
mentioning
confidence: 94%
“…It was reported to inhibit apoptosis of CD8+ tumor infiltrating lymphocytes and CD8+ tumor induced lymphocytes and increases CD8+ memory T cells. 58,59 Some studies suggested that metformin may sensitize cancer cells to some chemotherapy agents, including cisplatin, doxorubicin and paclitaxel. 34,55,60 Metformin was also found to increase radiosensitivity of cancer cells through ATM and AMPK.…”
mentioning
confidence: 99%
“…Eligible trials also showed no significant effect of metformin on all-cause mortality [28]. Nevertheless, metformin has been tried with some success in clinical chemotherapy trials for treatment of various types of cancer, and many trials are ongoing, including for breast, prostate, colorectal, pancreas, and lung cancers [29].…”
mentioning
confidence: 99%